2021
DOI: 10.1038/s41598-021-97294-4
|View full text |Cite
|
Sign up to set email alerts
|

Reduced mitochondrial fission and impaired energy metabolism in human primary skeletal muscle cells of Megaconial Congenital Muscular Dystrophy

Abstract: Megaconial Congenital Muscular Dystrophy (CMD) is a rare autosomal recessive disorder characterized by enlarged mitochondria located mainly at the periphery of muscle fibers and caused by mutations in the Choline Kinase Beta (CHKB) gene. Although the pathogenesis of this disease is not well understood, there is accumulating evidence for the presence of mitochondrial dysfunction. In this study, we aimed to investigate whether imbalanced mitochondrial dynamics affects mitochondrial function and bioenergetic effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…For example, alterations in mitochondrial DNA are associated with myofiber atrophy and decreased muscle regenerative capacity in sarcopenia 40,41 . Furthermore, muscle wasting in several types of muscular dystrophies is related to loss of mitochondrial and oxidative gene expression and mitochondrial dysfunction 42–44 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, alterations in mitochondrial DNA are associated with myofiber atrophy and decreased muscle regenerative capacity in sarcopenia 40,41 . Furthermore, muscle wasting in several types of muscular dystrophies is related to loss of mitochondrial and oxidative gene expression and mitochondrial dysfunction 42–44 …”
Section: Discussionmentioning
confidence: 99%
“…40,41 Furthermore, muscle wasting in several types of muscular dystrophies is related to loss of mitochondrial and oxidative gene expression and mitochondrial dysfunction. [42][43][44] Previous transgenic overexpression studies showed that both ERRs positively regulated the formation of type IIA and IIX (oxidative) myofibers in the skeletal muscle, and suppress the formation of type IIB (glycolytic) myofibers. 10,19 In contrast, deletion of ERRs in the DKO muscles results in an increased type IIA and decreased type IIX myofibers without affecting type IIB myofibers.…”
Section: Discussionmentioning
confidence: 99%
“…In contrary, in most TEM micrographs, the control group displayed arranged, aggregated and elongated-shaped mitochondria that occasionally isolate neighbouring myofibrils ( Figure 3 A,B). Given the importance of size and the round shape of the mitochondria in muscle pathologies [ 85 , 86 , 87 , 88 ], we attempted to quantify surface area (size) and count the number of the round-like shaped mitochondria using ImageJ. Interestingly, in contrast to the control group, the fluvastatin-treated flies showed significantly larger mitochondria sizes ( Figure 3 E) and the number of round-like shaped mitochondria was remarkably higher ( Figure 3 F).…”
Section: Resultsmentioning
confidence: 99%
“…Our data shows significantly increased inositol for all defects compared to controls while AMP was generally decreased relative to controls. Since reduced mitochondrial fission is linked to impaired energy metabolism 29 it is possible that the measured inositol and AMP levels in defects are reflective of the reduced OXPHOS activity observed in all defects (cf. OCR levels in Figure 1).…”
Section: Discussionmentioning
confidence: 99%